2017
DOI: 10.3390/ijms18122635
|View full text |Cite
|
Sign up to set email alerts
|

Diphlorethohydroxycarmalol from Ishige okamurae Suppresses Osteoclast Differentiation by Downregulating the NF-κB Signaling Pathway

Abstract: Marine algae possess a variety of beneficial effects on human health. In this study, we investigated whether diphlorethohydroxycarmalol (DPHC), isolated from Ishige okamurae, a brown alga, suppresses receptor activator of nuclear factor-κB ligand (RANKL)-induced osteoclast differentiation. DPHC significantly suppressed RANKL-induced osteoclast differentiation and macrophage-colony stimulating factor (M-CSF) expression in a dose-dependent manner. In addition, it significantly inhibited actin ring formation, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 29 publications
(32 reference statements)
0
16
0
Order By: Relevance
“…RANK is located in the cell membrane of osteoclasts and facilitates osteoclast activation and differentiation . RANKL was declared to accelerate bone resorption and depression of NF‐κB pathway represses osteoclast differentiation . All the above demonstrations provided evidence that the NF‐κB pathway plays an important role in OP progression and makes simulative effects on bone resorption and activation of OP.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…RANK is located in the cell membrane of osteoclasts and facilitates osteoclast activation and differentiation . RANKL was declared to accelerate bone resorption and depression of NF‐κB pathway represses osteoclast differentiation . All the above demonstrations provided evidence that the NF‐κB pathway plays an important role in OP progression and makes simulative effects on bone resorption and activation of OP.…”
Section: Discussionmentioning
confidence: 90%
“…3 RANKL was declared to accelerate bone resorption and depression of NF-κB pathway represses osteoclast differentiation. 36,37 All the above demonstrations provided evidence that the NF-κB pathway plays an important role in OP progression and makes simulative effects on bone resorption and activation of OP. In the present study, we found that the NF-κB pathway could be inhibited by CST5 up-regulation and by which mechanism the progression of OP was impeded.…”
Section: Discussionmentioning
confidence: 91%
“…RANKL/RANK/osteoprotegerin (OPG) signaling plays a critical role in bone remodeling and suppression and this is effective in various bone diseases with increased bone loss in animal models [18]. Recently, diphlorethohydroxycarmalol, a phlorotanin isolated from brown alga (Ishige okamurae) brought about an antiosteoclastogenetic effect by suppressing RANKL/NF-κB signaling [19].…”
Section: Effect Of Ece On Osteoclast Differentiation and Bone Resorptmentioning
confidence: 99%
“…Additionally, phosphorylation of phospholipase Cc (PLCc) activates the Ca 2þ /NFATc1 signalling pathway, which is important in osteoclastogenesis [7]. RANKL also induces the expression of tartrate-resistant acid phosphatase (TRAP), which is a marker gene of osteoclastogenesis [8]. The regulatory mechanisms of osteoclast differentiation are complex.…”
Section: Introductionmentioning
confidence: 99%